Modeling the Feasibility of Fueling CNG Heavy-Duty Trucks in Toronto, Canada - Amal Ghamrawi; Hanna Maoh (Findings)
Compressed Natural Gas (CNG) is cleaner than diesel for powering heavy duty trucks. A framework for establishing mobile on-site CNG refueling at truck yards is proposed and evaluated for the Greater Toronto and Hamilton Area (GTHA), Canada. The locations for potential CNG hubs where mobile trailers obtain CNG to fuel parked trucks at yards were determined. Also, the demand representing parked CNG trucks was estimated across the GTHA. With 15 potential CNG hubs, location-allocation modeling suggests that one CNG hub located in the Peel region can cover 88% of the demand within a 30-minute driving window across the study area.